Pengaruh Celebrity Endorser dan Brand Trust terhadap Minat Beli Ulang pada Produk Bedak Padat Wardah di Kota Cimahi - Ufairoh, Zihan Aqilah; Ramli, Rosmini (Universitas Batanghari, 2024)
The purpose of the study was to test and determine the influence of Celebrity Endorser and Brand Trust on the interest to buy again for users of Wardah compact powder products. The approach applied is a quantitative method through the use of primary data obtained from questionnaires. The number of samples in this study there are 90 respondents through the use of technical purposive sampling, then the data were analyzed using SPSS data processing version 25. The specified population is consumers who have previously used solid powder products from Wardah domiciled in Cimahi. The resulting research shows that celebrity endorser can influence the repurchase interest positively, brand trust can affect the repurchase interest positively, simultaneously celebrity endorser and brand trust can affect the repurchase interest.